The Role of Digital Public Relations in Sustaining Institutional Excellence in AR-Rasheed Modern Schools, Yemen (The International Journal of Educational Sciences and Arts, 2024)
The current study aimed to reveal the role of digital public relations in sustaining institutional excellence through applying it to AR-Rasheed Modern Schools in Yemen. It too adopted both the field method and the questionnaire as a tool for collecting data from a stratified random sample of (163) individuals from workers in seven branches of these schools. The results of this study showed practices of Public Relations Department at AR-Rasheed Schools for its activities, digitally, to a “high” degree. While its indicators of sustainability of institutional excellence are available in these schools to a “high” degree. It was apparently shown that there is a positive, strong and significant direct correlation at (0.01) between digital public relations activities and indicators of sustainability of institutional excellence. It also depicted that there is a positive and strong significant effect (0.05) of digital public relations activities on sustaining institutional excellence. The study finally recommended the importance of activating the role of Public Relations Department in directing its digital activities towards enhancing the sustainability of institutional excellence in the long term.
Keywords: Public Relations Department; Digital Practices; Sustaining Institutional Excellence; AR-Rasheed Modern Schools-Yemen